Ladder-like polysilsesquioxane dielectrics for organic field-effect transistor applications - Pei, Mingyuan; Lee, Albert S.; Hwang, Seung Sang; Yang, Hoichang (ROYAL SOC CHEMISTRY, 2017)
A series of trimethylsilyl-capped hybrid ladder-like polysilsesquioxane (LPSQ-TMS) derivatives were synthesized comprising an inorganic backbone functionalized with various organic side moieties and compositional ratios with application towards gate dielectrics or surface modifying materials. The surface energy (gamma) and roughness (R-q) values of the LPSQ-TMS coated SiO2 dielectrics were considerably affected by the side moieties of the polymer series; methyl, n-propyl, phenyl (P), naphthyl (N), methacryloxypropyl (MA), and fluorooctyl moieties. The gamma values varied from 17.0 to 42.0 mJ m(-2), while the R-q values also ranged from 0.34 to 1.10 nm. On polymer-treated SiO2 dielectrics possessing smooth and semiconductor-compatible surface properties, pentacene developed terrace-like crystallites formed through layer-by-island growth modes, a stark contrast to the three-dimensionally grown crystal islands formed on rough or extremely hydrophobic surfaces, which led to unfavorable conduction pathways. Depending on the order of conjugation and interconnections between the pentacene domains, the average mobility (mu(FET)) values of the resulting 50 nm thick pentacene organic field-effect transistors were varied by two orders of magnitude and reached 0.8 cm(2) V-1 s(-1), specifically, for both the P- and MA-substituted LPSQ-TMS treated SiO2 dielectrics (gamma = 37.0 mJ m(-2) and R-q = 0.40 nm). Moreover, we were able to demonstrate that a thermally cured 500 nm thick LPSQ-TMS layer on an Au gate-patterned flexible polyimide substrate could yield pentacene OFETs with mFET values as high as 0.60 cm(2) V-1 s(-1), comparable to that of the LPSQ-TMS treated SiO2 system. Also, the proper introduction of organic substituents to LPSQ improved the gate-bias stress stability for high performance OFETs.
Keywords: THIN-FILM TRANSISTORS; POLYMER BLEND SEMICONDUCTORS; GATE-DIELECTRICS; PENTACENE; PERFORMANCE; GROWTH; MOBILITY; NANOSTRUCTURES; DEPENDENCE; ROUGHNESS